I need some help in determining how the following equation develops from this: T= 2 Pi r / (Sq. root of r X g) to: T= 2 Pi X (sq root r/g). How do we get the quantity (Sq. root r X g) in the denominator to (Sq. root r/g) in the numerator? I multiplied the numerator and denominator of the right side of the original equation by Sq. root r X g to get T= 2 Pi r X Sq root r X g in the numerator, and r X g in the denominator (eliminating radical in denominator). Now, the r in the denominator cancels the r in the numerator, giving T= 2 Pi Sq root r X g / g. I don't understand how the equation becomes T= 2 Pi X Sq. root r/g (now no denominator). Any help will be appreciated.